CYP2D6 gene polymorphism and apatinib affect the metabolic profile of fluvoxamine - Ye, Zhize; Chen, Bingbing; Gao, Nanyong; Kong, Qihui; Hu, Xiaoqin; Lu, Zhongqiu; Qian, Jianchang; Hu, Guoxin; Cai, Jianping; Wu, Bin (Frontiers in Pharmacology, 2022)
This study aimed (i) to investigate the influence of CYP2D6 variants on the catalyzing of fluvoxamine, and (ii) to study the interaction between fluvoxamine and apatinib. An enzymatic reaction system was setup and the kinetic profile of CYP2D6 in metabolizing fluvoxamine was determined. In vivo, drug-drug interaction was investigated using Sprague–Dawley (SD) rats. Fluvoxamine was given gavage with or without apatinib. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to determine the concentrations of fluvoxamine and desmethyl-fluvoxamine. The results demonstrated that the relative clearance rates of CYP2D6.A5V, V104A, D337G, F164L, V342M, R440C and R497C increased significantly compared with CYP2D6.1, ranging from 153.626±6.718% to 394.310±33.268%. The activity of other variants was reduced more or less, or even lost function, but there was no statistical difference. The IC50 of apatinib against fluvoxamine disposition was determined, which is 0.190 μM in RLM and 6.419 μM in HLM, respectively. In vivo, apatinib can enhance the plasma exposure of fluvoxamine remarkably characterized by increased AUC, Tmax and Cmax. Meanwhile, the produce of desmethyl fluvoxamine was dramatically inhibited, both AUC and Cmax decreased significantly. Mechanistically, apatinib inhibit the generation of fluvoxamine metabolite with a mixed manner both in RLM and HLM. Furthermore, there were differences in the potency of apatinib in suppressing fluvoxamine metabolism among CYP2D6.1, 2 and 10. In conclusion, CYP2D6 gene polymorphisms and drug-drug interaction can remarkably affect the plasma exposure of fluvoxamine. The present study provides basis data for guiding individual application of fluvoxamine.